Analisis Kebutuhan Pembangunan Tempat Pemakaman Umum di Perkotaan Tuban - Arwi Yudhi Koswara; Eko Budi Santoso; Abdul Afif; Teti Hariyati; Sutikno Sutikno; Ema Umilia; Prianti Prianti; Rahel Putri Pamungkas; Chichik Ilmi Annisa (TATALOKA, 2021)
The land availability in public cemeteries in Tuban currently under pressure towards the land capacity which is getting limited due to the population growth and inadequate facilities. This study, using the calculation to get the estimated area and the land capacity of the public cemetery in Tuban. The data compilation steps consists of primary survey and secondary survey. The primary survey activities carried out included field surveys and community aspirations which were carried out through in-depth interviews and Focus Group Discussions (FGD). Meanwhile, the secondary survey was conducted to find data, namely basic data on laws and policies, and data on social demographic conditions. The analytical method used is the analysis of grave needs by analyzing the projection of the mortality rate, calculating the need for cemetery land area per year, calculating the remaining land area for the cemetery, calculating the remaining land capacity of the cemetery, and calculating the remaining capacity of the cemetery with a one-time overlapping system. From the results of the analysis, it is obtained that the remaining capacity of the burial ground in Tuban District will be filled in 2021 and will require an additional land area of 617,945 m2 (61 Ha) in 2030. Semanding and Merakurak Districts are projected to be full in 2025 with a land area requirement of 81,589 m2 (8.1 Ha) and 113,875 m2 (11 Ha) in 2030 Palang District will be full in 2026 and Jenu District will be full in 2028.